Analiza porównawcza cen i stóp zwrotu na wtórnym rynku lokali mieszkaniowych - Cegielski, Piotr; Ślufarska, Magdalena (Comparative Analysis of Prices and Rate Of Return on the Residential Secondary Market, 2008)
In 2006-2007 the residential market was characterized by substantial dynamic, however depending on the locality and type of apartment different phenomenon were observed. In the article the authors conduct the comparative analysis of selected segments on the residential market, in regard to the localization (Wrocław, Cracow), as well as from the point of view of other fundamental market features (localization within the city, implementation of constructional and material technology, age of the buildings), with regard to the market transactional prices. The analysis allow to make the conclusion, that both markets (in Wrocław and Cracow) show some similarities in regard to general tendencies, such us growth in prices, the attractiveness of particular apartments, or progressing segmentation on the market of apartment's purchasers. The results of the analysis let to formulate the conclusion, that in the considered time period both markets were on the different stage of development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 9-18